Quality control, modeling, and visualization of CRISPR screens with MAGeCK-VISPR. Issue 1 (December 2015) - Li, Wei; Köster, Johannes; Xu, Han; Chen, Chen-Hao; Xiao, Tengfei; Liu, Jun; Brown, Myles; Liu, X.
Abstract High-throughput CRISPR screens have shown great promise in functional genomics. We present MAGeCK-VISPR, a comprehensive quality control (QC), analysis, and visualization workflow for CRISPR screens. MAGeCK-VISPR defines a set of QC measures to assess the quality of an experiment, and includes a maximum-likelihood algorithm to call essential genes simultaneously under multiple conditions. The algorithm uses a generalized linear model to deconvolute different effects, and employs expectation-maximization to iteratively estimate sgRNA knockout efficiency and gene essentiality. MAGeCK-VISPR also includes VISPR, a framework for the interactive visualization and exploration of QC and analysis results. MAGeCK-VISPR is freely available athttp://bitbucket.org/liulab/mageck-vispr .